The effectiveness of tuberculosis (TB) education intervention programme on knowledge, attitude, practice and stigma about TB among secondary school students in Kelantan - Idris, Nur Aiza (2020)
Introduction Tuberculosis (TB) is a major health problem affecting millions of people every year worldwide. In Malaysia, despite having a comprehensive TB control program, the number of TB cases is still alarming, including cases among adolescents. About 8.5% of TB cases in Malaysia were children and adolescent with highest TB incidence between age group of 10 to 19. The current scenario indicates that innovative interventions among adolescents have to be taken seriously for its effective disease control. The need for school intervention programme is crucial as TB can extensively spread in congregate settings like school environment, thus it creates challenges for TB control. Health education programme could streamline accurate information and facilitate health-seeking behaviours among adolescents towards TB, which will help in control and end the TB. Objective To determine the effectiveness of TB education programme on knowledge, attitude, practice and stigma among secondary school student in Kelantan. Methodology This study was a school-based interventional study (nonrandomized trial) conducted among secondary school students from two districts in Kelantan. The students were selected by using cluster sampling among second form (14- year-olds) and fourth form (16-year-olds) students. The intervention group received TB education program consisted of a lecture, quiz, small group discussion, posters exhibition and printed materials on TB while the control group received information on adolescent health and hygiene. Their knowledge, attitude, practice, and stigma score were assessed before and one month after the program using validated structured questionnaire. Repeated measures ANOVA were applied. Results A total of 236 secondary school students were involved with majority of them were Malay and female predominant. The mean percentage score (SD) for baseline knowledge, attitude, practice and stigma score for the respondents were 54.0 (4.48), 65.6 (1.74), 70.0 (1.43) and 66.0 (6.88) respectively. There was a significant difference (p < 0.001) in the knowledge and stigma score for intervention group compared to control group, adjusted for gender, ethnicity and smoking status 4 weeks post TB educational programme. However, with regards to attitude and practice score, there was no significant difference (p = 0.210 and p = 0.243, respectively) comparing both groups. Conclusion The baseline adolescents in the present study were found to have average levels of knowledge and preventive practices with regards to TB. Overall, they had positive attitudes toward TB disease; however, the level of negative stigma against TB was high. This TB education intervention progamme has been shown to be effective in improving the knowledge and stigma regarding TB among secondary school students. This health education program can be used as one of the strategies for the prevention and control of TB in Malaysia, especially in schools.